Toward the end of the Corporate Social Performance – Corporate Financial Performance debate - Soriano, Luis; Fong, Carlos (Business: Theory and Practice, 2023)
The purpose of this document is to present the way forward to finalize the debate related to the link between Corporate Social Performance – Corporate Financial Performance. The discussion and proposal of 7 elements were developed that allow proposing a new methodological path for the development of empirical investigations that seek to explain the link between the Corporate Social Performance – Corporate Financial Performance. After the theoretical review, it was found that the most relevant changes were associated with the level of maturity of the Corporate Social Performance, micro-foundations approach, mediating variables, structural equation models, primary sources, and delimitation of the short, medium, and long term on the analysis.